Laryngeal schwannoma – A case report with short literature review - Relić, Nenad; Jevtić, Milica; Belić, Branislav; Petrović Rodić, Dušica; Jevtović, Andra; Božović, Natalija; Jovanović, Marina; Stojanović, Jasmina (Vojnosanitetski pregled, 2022)
Introduction. Laryngeal schwannomas are rare benign neurogenic tumors. They are usually localized in the supraglottic portion of the larynx. We reported a rare case of laryngeal schwannoma with a focus on clinical presentation, diagnosis and management. Case report. A 61-year old male patient with a 3-year history of hoarseness underwent telescopic examination which revealed an oval submucosal tumefaction of the left ventricular fold extending over the left vocal fold toward the right ventricular fold. Multislice computed tomography showed a 22 x 15 mm well defined, oval heterodense mass in the region of the left ventricular fold, extending toward the left vocal fold and the posterior commissure of the larynx, with signs of initial compression lesion of the thyroid cartilage. Biopsy and histopathology revealed a primary benign encapsulated mesenchymal tumor, while immunohistochemistry analysis confirmed schwannoma diagnosis. The patient underwent tracheotomy and left hemilaryngectomy, with complete removal of the tumor. There were no signs of recurrence at the six-month follow-up. Conclusion. Schwannomas are rare among benign tumors of the larynx and might grow for years before being diagnosed. Biopsy with histopathology analysis is used to confirm the diagnosis of laryngeal schwannoma, although extreme care should be taken during biopsy. Treatment consists of complete surgical excision; the surgical approach depends on the size and localization of the tumor, as well as on the presence of a peduncle.